If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 6(x + 8) + 8 Reorder the terms: 5x = 6(8 + x) + 8 5x = (8 * 6 + x * 6) + 8 5x = (48 + 6x) + 8 Reorder the terms: 5x = 48 + 8 + 6x Combine like terms: 48 + 8 = 56 5x = 56 + 6x Solving 5x = 56 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5x + -6x = 56 + 6x + -6x Combine like terms: 5x + -6x = -1x -1x = 56 + 6x + -6x Combine like terms: 6x + -6x = 0 -1x = 56 + 0 -1x = 56 Divide each side by '-1'. x = -56 Simplifying x = -56
| 3(x+1)=2x+7 | | 34-69=5(x-3) | | 2(x+5)=6 | | 2x(x+5)=6 | | 9y-14=8y-1 | | -25=10p | | -48=5y+y | | 3x+3-2x=6-20 | | 3x-0.4=x-0.1 | | -8+23=12x-2-11x | | 3x-0.4= | | (1.15+8x)=(2.3-1.5x) | | 6x-3-5x-5=26 | | 3(2b+1)-7=50 | | 13x-18=4(3x-1)+5 | | 55=4+3(m+2) | | 25-2(t-5)=19 | | 8(2c-1)=56 | | 5(x+2)=20 | | x+(4x+32)=12 | | 4x+3=-5 | | 4x+10+13x=180 | | 3(x-5)-1=2x+6 | | 4x+10+13=180 | | 4x-10+13x=180 | | 52-5x=4x+19 | | 8-9x=56-30x | | -13-7x=8x+17 | | 17+3(3x-1)=7x-18-2x | | 4x+12=-66-9x | | 96-4x=2x+6 | | -30-2x=12-9x |